A Structured Transfer of Care Process Reduces Perioperative Complications in Cardiac Surgery Patients. Issue 5 (October 2017) - Hall, M.; Robertson, J.; Merkel, M.; Aziz, M.; Hutchens, M.
Abstract : (Abstracted from Anesth Analg, 125(2):477–482, 2017) The implementation of a standardized, uncomplicated, and easy-to-teach protocol to be followed when transitioning patients from the operating room to the intensive care unit (ICU) could result in more effective communication and teamwork, thus reducing risks of perioperative complications. This study aimed to assess whether the introduction of a comprehensive multidisciplinary transfer of care protocol improved patient outcomes by examining them before and after the introduction of the patient handoff protocol.